Evaluation of the Haemodynamic and Metabolic Effects of Local Anaesthetic Agent in Routine Dental Extractions (2013)
Introduction: The systemic effects of adrenaline adminisitered during dental local anesthesia have been the subject of many studies. The purpose of this study was to investigate the haemodynamic and metabolic effects attributable to adrenaline injected during local anesthesia in dental extraction patients. Methods Apparently medically fit patients were included and randomized into two groups. Participants had breakfast before coming in for tooth extraction. The weight, height, blood pressure and pulse rate were measured and blood sample taken before administration of local anaesthetic injections. Blood pressure, pulse and blood sample were again taken at 15 and 30 min. Results: While the adrenaline group showed a modest increase between pre- and post-drug administration states, the control group showed no difference in median systolic blood pressures. Both groups showed a slight increase in diastolic blood pressure observed between pre- and post drug administration states. Also both groups showed no significant difference in median pulse rate throughout. Although blood glucose values were widely dispersed in the pre-drug administration state in both groups, the control group showed no difference in median values throughout. However, a modest increase was observed in the adrenaline group between pre- and post-drug administration states, which persisted beyond 30 min. Conclusion: The patients treated with local anesthesia with adrenaline showed a response similar to that observed in the control group.